2020
DOI: 10.3389/fimmu.2020.588079
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic View of Berberine Inhibiting Intestinal Carcinogenesis in Conventional Mice Based on Microbiome-Metabolomics Analysis

Abstract: Berberine (BBR) has been reported that it has effects on inhibiting colorectal cancer (CRC). However, the mechanism of BBR on CRC also remains largely unknown. Herein, we investigated the therapeutic effects of BBR on CRC from the perspective of gut microbiota and metabolic alterations, which can provide a holistic view to understand the effects of BBR on CRC. First, azoxymethane (AOM)/dextran sodium sulfate (DSS) mouse was used as CRC animal model, then the degree of colorectal carcinogenesis in AOM/DSS mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 61 publications
1
42
1
Order By: Relevance
“…The results indicated that berberine intervention along with the reduction of intestinal tumor development could improve metabolic abnormalities by reversing glucose metabolism (glycolysis/gluconeogenesis, fructose and mannose, and galactose), amino acid-related metabolism (lysine degradation), and lipid metabolism (fatty acid biosynthesis and arachidonic acid). In vivo animal models confirmed the above mechanisms by analyzing a total of 8 DMs from the detected 44 of fecal metabolites regulated by berberine in the azoxymethane/DSSinduced CRC mouse model (Chen et al, 2020b). To uncover the interactions of DMs and further investigate the underlying mechanisms of action of berberine against prostate cancer, bioinformatics analysis was performed to identify the functions of metabolites using Ingenuity Pathway Analysis (IPA) software .…”
Section: Metabolomicsmentioning
confidence: 97%
See 1 more Smart Citation
“…The results indicated that berberine intervention along with the reduction of intestinal tumor development could improve metabolic abnormalities by reversing glucose metabolism (glycolysis/gluconeogenesis, fructose and mannose, and galactose), amino acid-related metabolism (lysine degradation), and lipid metabolism (fatty acid biosynthesis and arachidonic acid). In vivo animal models confirmed the above mechanisms by analyzing a total of 8 DMs from the detected 44 of fecal metabolites regulated by berberine in the azoxymethane/DSSinduced CRC mouse model (Chen et al, 2020b). To uncover the interactions of DMs and further investigate the underlying mechanisms of action of berberine against prostate cancer, bioinformatics analysis was performed to identify the functions of metabolites using Ingenuity Pathway Analysis (IPA) software .…”
Section: Metabolomicsmentioning
confidence: 97%
“…In fecal or mucosal samples, berberine treatment greatly rescues colorectal tumorigenesis by improving the imbalance of the gut microbiota and modulating the tumor microenvironment by decreasing the richness of microbiota community and relative abundance of Actinobacteria and Verrucomicrbia at the phylum level, as well as suppressing pathogenic species (e.g., F. nucleatum , f_ Erysipelotrichaceae and Alistipes ) and elevating some bacteria producing short-chain fatty acid (SCFA) ( Alloprevotella , Flavonifractor and Oscillibacter ) at the genus level in AOM/DSS-induced CRC mouse model ( Yu et al, 2015 ; Chen et al, 2020b ). Interestingly, exercise therapy combined with berberine treatment produces the lowest effects on species richness and the highest relative abundance of bacteroidaceae to achieve a synergistic anticancer effect, compared with negative control and single administration in 4T1 breast cancer-bearing mice ( Ma et al, 2020 ).…”
Section: Omics Studiesmentioning
confidence: 99%
“…[ 89 ] Another study indicated that BBR could induce alterations in the composition of the gut microbiota and bacterial metabolism in AOM/DSS mice, leading to inhibition of colorectal tumorigenesis. [ 90 ] Sini decoction (SND) is a classic prescription of TCM. SND extract can ameliorate the degree of tumor malignancy in AOM/DSS mice.…”
Section: Strategies Of Microbe-based Managementmentioning
confidence: 99%
“…The method of fecal sample preparation was described in a previous study [29]. Brie y, 100 mg thawed stool material were mixed with 0.8 mL PBS containing 10% deuterated water (D2O 99.8%; SIGMA, United States) and 0.05 mM sodium 3-trimethylsilyl-propionate-d4 (TMSP-2,2,3,3-d4; SIGMA, Untied States) as a chemical shift reference.…”
Section: Fecal Samples Preparation For 1 H-nmr Analysismentioning
confidence: 99%